Multimodal deep learning model for prognostic prediction in cervical cancer receiving definitive radiotherapy: a multi-center study - Weiping Wang; Guang Yang; Yulin Liu; Lichun Wei; Xiaoying Xu; Chulong Zhang; Zhaohong Pan; Yongguang Liang; Bo Yang; Jie Qiu; Fuquan Zhang; Xiaorong Hou; et al. (npj Digital Medicine)
Abstract For patients with locally advanced cervical cancer (LACC), precise survival prediction models could guide personalized treatment. We developed and validated CerviPro, a deep learning-based multimodal prognostic model, to predict disease-free survival (DFS) in 1018 patients with LACC receiving definitive radiotherapy. The model integrates pre- and post-treatment CT imaging, handcrafted radiomic features, and clinical variables. CerviPro demonstrated robust predictive performance in the internal validation cohort (C-index 0.81), and external validation cohorts (C-index 0.70&0.66), significantly stratifying patients into distinct high- and low-risk DFS groups. Multimodal feature fusion consistently outperformed models based on single feature categories (clinical data, imaging, or radiomics alone), highlighting the synergistic value of integrating diverse data sources. By integrating multimodal data to predict DFS and recurrence risk, CerviPro provides a clinically valuable prognostic tool for LACC, offering the potential to guide personalized treatment strategies.